On the hydrodynamic mutual interactions among cells for high-throughput microfluidic holographic cyto-tomography. (November 2022) - Pirone, Daniele; Villone, Massimiliano Maria; Memmolo, Pasquale; Wang, Zhe; Tkachenko, Volodymyr; Xiao, Wen; Che, Leiping; Xin, Lu; Li, Xiaoping; Pan, Feng; Ferraro, Pietro; Maffettone, Pier Luca
Highlights: The dynamic of the rotation of adjacent cells in a tomographic flow cytometer is investigated with the aim to prevent mutual disturbing effects among them. Both numerical simulation of the fluid dynamics and experimental data show that such hydrodynamic interactions are negligible, as they do not affect the possibility of recovering reliable tomograms. The optimum density of cells can be estimated to allow the calculation of the maximum achievable throughput. Abstract: In digital holography (DH) modality for lab on chip application the cells passing through the field of view (FOV) of the microscope can be detected and analyzed even if they are flowing at different depths. In fact, in-focus imaging of each cell can be easily retrieved thanks to the ability of DH to obtain numerical focus ex-post the recording process. An advantageous and preferred configuration for DH in flow-cytometry modality provides that the cells rotate along the microfluidic channel. This gives the unique chance to probing cells by light beams alongside many different directions while they cross the holographic FOV. Thus, it is possible to retrieve the 3D refractive index map of each flowing cell, i.e. a 3D phase-contrast tomogram. Although many cells can be analyzed in the same FOV, thus giving the possibility to increase the throughput of the system, until now no investigations have been made to establish how close the cells can be to avoid mutual disturbing effects on their rotation. Nevertheless, to estimate the maximum achievable throughput, it is indispensable to comprehend the effects of hydrodynamic interactions on adjacent cells in a tomographic flow cytometer. Here we show by means of an experimental and a numerical simulation of the fluid dynamics that hydrodynamic interactions have a quantitative effect on cells rotational behavior and neither on their mechanical deformation. However, in the considered scenario we demonstrate that the effect is negligible as it does not affect the possibility of recovering the tomograms. The reported results will allow to estimate which is the optimum density of cells to analyze by the holographic flow-cyto-tomograph thus opening the route for biomedical applications.